The Effectiveness of a Play Based Social Emotional Program on Mathematics and English Language Learning Readiness in Early Childhood Education - Dwi Adhinda Junaidi Putri; Ivvon Septina Bella; Tri Putri Utami (STMIK Indonesia Banda Aceh, 2026)
This study examines the effectiveness of a play-based social-emotional program on mathematics and English language learning readiness in early childhood education. Learning readiness at this stage is influenced not only by cognitive abilities but also by social-emotional competencies such as self-regulation, attention, cooperation, and confidence. A quasi-experimental design with a pretest–posttest control group was employed. Participants were children aged 5–6 years divided into an experimental group and a control group. The experimental group received a play-based social-emotional program integrated into daily learning activities, while the control group followed conventional instruction. Data were collected using social-emotional observation sheets, mathematics readiness assessments, and English language learning readiness assessments. Data were analyzed using descriptive statistics and independent samples t-tests. The results showed that children in the experimental group demonstrated significantly higher readiness to learn mathematics and English compared to the control group. These findings indicate that integrating social-emotional learning into play-based activities effectively supports holistic learning readiness in early childhood education.